2012
DOI: 10.1136/thoraxjnl-2011-200266
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of clinical outcome in a national hospitalised cohort across both waves of the influenza A/H1N1 pandemic 2009–2010 in the UK

Abstract: BackgroundAlthough generally mild, the 2009–2010 influenza A/H1N1 pandemic caused two major surges in hospital admissions in the UK. The characteristics of patients admitted during successive waves are described.MethodsData were systematically obtained on 1520 patients admitted to 75 UK hospitals between May 2009 and January 2010. Multivariable analyses identified factors predictive of severe outcome.ResultsPatients aged 5–54 years were over-represented compared with winter seasonal admissions for acute respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
84
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 26 publications
16
84
1
1
Order By: Relevance
“…Although individual risk for mortality is low, a significant subset of infected patients develop pneumonia, the most lethal consequence of influenza (5). Those at the highest risk for infection and complications include pregnant women (6), the elderly (>65 y) (7), the very young (<5 y of age, and especially less than 2 y), smokers (8), those exposed to inhaled toxicants such as oxygen (9) and air pollutants (10), and patients with chronic illnesses such as diabetes and emphysema (11,12). Increased risk is often ascribed to impairment of the immune system, and differential susceptibility of the airway epithelium is seldom considered in mechanistic studies of host factors that predispose to IAV infection and poor outcomes.…”
mentioning
confidence: 99%
“…Although individual risk for mortality is low, a significant subset of infected patients develop pneumonia, the most lethal consequence of influenza (5). Those at the highest risk for infection and complications include pregnant women (6), the elderly (>65 y) (7), the very young (<5 y of age, and especially less than 2 y), smokers (8), those exposed to inhaled toxicants such as oxygen (9) and air pollutants (10), and patients with chronic illnesses such as diabetes and emphysema (11,12). Increased risk is often ascribed to impairment of the immune system, and differential susceptibility of the airway epithelium is seldom considered in mechanistic studies of host factors that predispose to IAV infection and poor outcomes.…”
mentioning
confidence: 99%
“…In a study on the pediatric age group, asthma and neurologic impairment were the most prevalent underlying risk factors (22). Regarding the role of obesity and being overweight, there are established evidences concerning the place of high BMI in severity of disease (19,23,24). In our study, BMI was shown to be an independent risk factor of Hypoxemia in the course of the 2009 pandemic influenza A (H1N1).…”
Section: Discussionmentioning
confidence: 58%
“…While influenza A infection, including the H1N1 2009 pandemic, is associated with greater morbidity and mortality among patients with asthma as compared to the general population [7,8], among those hospitalised for pandemic influenza, the presence of asthma has been associated with less severe outcomes [9]. This is in contradistinction to obesity, for example, which is associated with an important increase in severe outcomes, including death [9].…”
mentioning
confidence: 66%